Application and performance assessment of a Reflux Classifier for iron ore particle classification - Zhiyuan Zhang; Mengqi Ma; Lingfeng Xiang; Yanfeng Li (Minerals Engineering, 2026)

Largemouth bass virus infection subverts immune-redox homeostasis in zebrafish and is associated with coordinated suppression of NF-κB and Nrf2 signaling - Lingfeng Guan; Xinyue Zhang; Ting Yu; Yang Liu; Jiamei Long; Runchang Zhou; Hua Huang; Jinglin Tan; Zhifeng Chen; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2026)

Wearable triboelectric sensor based on a single-line-contact electrode architecture for gesture recognition and human–machine interaction - Long Li; Jingyun Dai; Jiayang Lyu; Yifan Shen; Yanmin Guo; Lingfeng Du; Zhiqian Wei; Xiongtu Zhou; Yongai Zhang; Hyung-Soon Kim; Dianlun Li; Kun Wang; et al. (Chemical Engineering Journal, 2026)

Advancing analysis of biofuel precursors from lignin: complete molecular characterization using GC × GC-FID - Linyu Zhu; Miloš Auersvald; Cunhao Cui; Yuhe Liao; Jing Zhang; Qing He; Lingfeng Li; Yi Ouyang; Zhongyue Zhou; Fei Qi; Kevin M. Van Geem (Fuel, 2026)

Biphasic multiplex PCR based on bead array for high-throughput and sensitive authentication of meat products - Lingfeng Yan; Rong Cao; Jiajin Wei; Hehui Long; Liming Zhang; Zhuoxuan Lu (Food Control, 2026)

Integrating enzymatic activity into highly emissive metal-organic frameworks derived from AIE ligands via horseradish peroxidase immobilization for dual-mode optical sensing - Zuyao Fu; Lingfeng Yang; Yuanyuan Zhang; Xuanjun Zhang; Jing Xie; Zhaoyang Ding (Chemical Engineering Journal, 2026)

Global ammonia (NH3) retrieval from the FY-3F satellite hyperspectral infrared atmospheric sounder and performance assessment - Zhili Deng; Yapeng Wang; Minqiang Zhou; Ling Gao; Lin Chen; Xifeng Cao; Lingfeng Zhang; Yuhan Jiang; Haiyang Dou; Xingying Zhang (Atmospheric Environment, 2026)

Integrating machine learning and deep learning with multiple molecular fingerprints for topoisomerase I inhibitor screening and lead identification - Huang Zeng; Xuerou Zheng; Jiayao Liu; Shengyuan Zhang; Hua Nie; Nan Wang; Lingfeng Wu; Chunfang Liu; Ming Zhai; Hao Yang; Jiunlong Yang; Bo Qiu (Molecular Diversity, 2026)

Multi-objective optimization of ship resistance and seakeeping using an improved Voronoi-based parallel sequential sampling method - Dongqin Li; Yu Zhang; Yanqing Yin; Wenwen Chen; Bohan Wang; Zishuai Wang; Lingfeng Lu (Ocean Engineering, 2026)

Reverse flotation desilication of bauxite Ore: unraveling the mechanism of Cu(II)-SDSo in selective separation of kaolinite from diaspore - Boai Zhang; Lingfeng Shen; Honghu Tang; Jianjun Wang; Wei Sun; Jianyong He; Li Wang (Minerals Engineering, 2026)

From waste to thermal regulator: Upcycling preservative-treated wood into multifunctional composite phase change materials for sustainable thermal management - Zhenxin Zhang; Yanan Dong; Lingfeng Kong; Phuocthoi Hoang; Xiaoqi Zhao; Jinzhen Cao (Journal of Cleaner Production, 2026)

A one-stone-three-birds strategy: Manipulating sodiation depth of SnTe anode enabling fast ion conduction, shuttle avoidance, and sodium replenishment for durable sodium-ion batteries - Zhiming Jia; Guoping Liu; Xu Han; Gangyong Zhou; Haihui chen; Chunjiang Jin; Ting Liu; Lingfeng Xu; Renyun Kuang; Changwang Pan; Shengping Dai; Dingwa Zhang; et al. (Chemical Engineering Journal, 2026)

Strongly coordinating anions and cosolvent synergy enabled lithium metal batteries - Yutao Liu; Yi Li; LingFeng Zhang; Mengmeng Tan; QiXian Zhang; Wei Lü (Chemical Engineering Journal, 2026)

Nonclassical modes of subtropical Indian Ocean dipole identified by autoencoder and their distinct climatic impacts - Bicheng Huang; Lingfeng Zheng; Zengping Zhang; Tao Su; Guolin Feng; Zhonghua Qian; Yongping Wu (Climate Dynamics, 2026)

Effects of Salinity on Growth, Survival, Gonadal Development, and Immune-System Indicators of Crassostrea ariakensis - Xiaotong Li; Xue Zhang; Zhaoqi Liu; Lingfeng Kong (Journal of Ocean University of China, 2026)

Mechanisms of interlayer force transmission and slip surface penetration in pile-reinforced reservoir landslides with multi-sliding zones - Haojie Duan; Zongxing Zou; Yang Zhang; Lingfeng Wu; Jiang Li; Jianqiang Tao; Yikai Niu; Xinli Hu (Landslides, 2026)

Granular hydrogel gradient microenvironments drive functional osteochondral interface regeneration - Jing Wang; Wenbo Zhong; Chengxiang Sha; Yu Shen; Zhaowei Yin; Lingfeng Yuan; Bin Liang; Xi Zeng; Jing Zhang; Ziyi Yu (Chemical Engineering Journal, 2026)

Simple and large-scale preparation of HPAMAM/PVA sponge with robust mechanical properties for hexavalent chromium adsorption - Ji Gao; Li Cai; Lingfeng Zhang; Cunwei Fan; Hao Zhang; Jie Sun; Kai Guo (Journal of Environmental Chemical Engineering, 2026)

Modelling and operation performance of the hybrid borehole heat exchangers constituted of a shallow U-pipe array and medium-deep coaxial pipe - Shilong Yang; Yaru Li; Lingfeng Huang; Qingbo Yang; Ke Zhu; Yudong Mao; Wenke Zhang; Mingzhi Yu (Energy and Buildings, 2026)

Dynamic risk assessment and early warning for water inrush during the excavation of karst river-crossing tunnels - Zengguang Xu; Zimeng Chen; Weili Ma; Fan Zhang; Lingfeng Zhao; Cheng Cao; Junrui Chai; Fajian Jin (Carbonates and Evaporites, 2026)

HMGB1 blockade attenuates cardiac injury induced by radiotherapy combined with PD-1 inhibitor while maintaining the anti-tumor efficacy - Yao Liu; Lingfeng Liu; Bibo Wu; Jing Zhang; Chaofen Zhao; Bing Lu; Yinxiang Hu; Weiwei Ouyang; Zhenneng Guo; Rong Hu; Shengfa Su (Apoptosis, 2026)

Co-exposure to polystyrene microplastics and perfluorooctanoic acid can exacerbate lipid metabolism disorders and liver damage in adult zebrafish - Sijie Tian; Ruixiang Li; Ya Zeng; Lingfeng Qin; Caicheng Long; Taiping Qing; Peng Zhang; Bo Feng (Journal of Environmental Sciences, 2026)

Development of a high-throughput sensitive SB-PCR assay for rapid detection of laboratory-escaped antibiotic resistance genes - Lingfeng Yan; Shengnan Liu; Rong Cao; Azadeh Nilghaz; Jiajin Wei; Hehui Long; Liming Zhang; Zhuoxuan Lu (Journal of Environmental Chemical Engineering, 2026)

Nickel incorporation engineering for synergistic regulation of oxygen vacancies and electronic band configuration in Bi2O3 nanosheets for high-performance supercapacitor electrodes - Lingfeng Li; Weihao Zhang; Xuexuan Luo; Xueyi Chang; Muqing Chen; Zhiyu Cheng; Yongfu Qiu; Yu Wang (Chemical Engineering Journal, 2026)

Long-Term in situ Monitoring of Anchoring System and Preliminary Analysis of Monitoring Data - Luobin Zheng; Huiming Tang; Liangqing Wang; Changdong Li; Chengren Xiong; Zongxing Zou; Chenlu Wang; Lingfeng Zhu; Yifan Zhang (Journal of Earth Science, 2026)

Leaf Size Variation in Response to Climate Drivers Depends on Plant Life Form - Jiayi Lu; Shihao Wen; Siyu Chen; Yuran Dong; Xiuping Wu; Yao Li; Min Zhang; Zhiwei Ge; Jonathan M. Chase; Lingfeng Mao (Journal of Biogeography, 2026)
Aim Plant leaf size and shape vary across major climatic gradients, reflecting the mechanisms for how plants regulate the balance of carbon, water, and heat. However, the influence of climate on leaf traits can be confounded by multiple factors, and the complex variation among different plant groups remains insufficiently understood. Here, we investigated how climate influences leaf size traits and whether this effect is moderated by plant life form. Location China. Taxon Angiosperms. Methods Based on leaf length, width, and aspect ratio data from 26,726 angiosperm species distributed across major climate gradients in China, we analysed the effects of temperature and precipitation on leaf size traits, and compared differences among plant life forms (woody vs. herbaceous and evergreen vs. deciduous). Additionally, spatial heterogeneity was assessed across eight vegetation zones. Results Leaves are generally larger and rounder in warm and humid areas, and smaller and narrower in cooler and more arid areas. All leaf size traits respond more strongly to precipitation than temperature, with leaf length showing the strongest responses to both climate variables. Herbaceous and deciduous species exhibit stronger climate responses nationwide, whereas woody and evergreen species are more sensitive within vegetation zones. Key responsive traits show clear geographic shifts. Main Conclusions Overall, we find that leaf size and shape vary strongly across China, as a result of climate variation, but these patterns are modified by dominant regional ecological processes and the ecological strategies of plant life forms. These findings not only help clarify variation in plant traits along climatic gradients, but also provide a theoretical framework for predicting how different plant morphologies will respond to ongoing climate change.

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Wheat density drives negative density dependence in nitrogen uptake and root plasticity in wheat–weed communities - Li Zhang; Weiqiang Liu; Yizhong Rong; Jiazhen Xi; Lingfeng Mao; Anna Gunina; Zhen Zhang (Rhizosphere, 2026)

Humic acid facilitates microbial manganese oxidation-driven arsenic remediation in soil across a wide temperature range - Weiwei Zhai; Wenjin Zhang; Lingfeng Dong; Yulong Ru; Yao Xu; Zhanfei He; Daoyong Zhang; Xiangliang Pan (Journal of Environmental Management, 2026)

A novel transformer-based CO2 retrieval framework incorporating prior constraint and hierarchical features injection: assessment of transferability for Tansat-2 - Lingfeng Zhang; Lu Zhang; Xingying Zhang; Tiantao Cheng; Xifeng Cao; Tongwen Li; Dongdong Liu; Yang Zhang; Yuhan Jiang; Ruohua Hu; Haiyang Dou; Lin Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Fibre–emulsifier interactions shape the lipid digestion behaviour of high internal phase emulsions - Yifeng Lu; Lingfeng Wu; Aprilia Nur Khasanah; Maarten Schutyser; Lu Zhang; Karin Schroën; Meinou Corstens (Food Hydrocolloids, 2026)

Multifunctional polyvinyl alcohol composites via melt blending with a bio-based P-N synergistic flame retardant: Achieving simultaneous enhancement in fire safety, UV shielding, and mechanical properties - Junsheng Guo; Wenzong Xu; Tao Yan; Jiayan Zhang; Xiaoyu Guo; Lingfeng Wang; Julan Liu (Chemical Engineering Journal, 2026)

Octonions and 7-dimensional space vector transformation - Lingfeng Liang; Hanwei Zhang; Kezhao Li; Hua Zhang (Applied Geophysics, 2026)

Three ectomycorrhizal fungal inoculum modifies the growth performance and tolerance of Quercus nuttallii seedlings under salt stress - Nan Yang; Cheng Wan; Daoyuan Ren; Yan Zhang; Stefano Chelli; Zhengxue Zhu; Silvia Traversari; Giovanni Emiliani; Lingfeng Mao (Forest Ecology and Management, 2026)

Polyphthalocyanine-based nanostructure for sono-immunotherapy by reprogramming the tumor microenvironment and blocking immune checkpoint - Lingfeng Jiang; Jiawei Wang; Wenjun Liu; Xin Xie; Xiao Luo; Ling Tu; Liangqing Tang; Qing Zhang; Hongmei Yuan; Hanfeng Yang; Qi Li; Sujiao Cao; et al. (Chemical Engineering Journal, 2026)

The sea level rise of the 8.2 ka event simulated by the iCESM1.3 - Lingfeng Wan; Zhengyu Liu; Chengfei He; Chenyu Zhu; Shaoqing Zhang; Jiuyou Lu; Zhaowei Jing (Climate Dynamics, 2026)

Towards adaptive management: Future environmental risk assessment of tailing ponds in China under SSP scenarios - Junhong Ling; Bolun Zhang; Zhenxiong Zhao; Lingling Liu; Da Lv; Soon Thiam Khu; Lingfeng Zhou; Xiaoli Zhao (Journal of Environmental Management, 2026)

Community assembly and nitrogen metabolic characteristics of size-fractionated microorganisms in floating bed restoration area - Yi Shi; Rui Zhao; Lingfeng Huang; Wenjing Zhang (Journal of Oceanology and Limnology, 2026)

Experimental and numerical study of a novel thin metal mesh infrared radiant burner - Jiarui Li; Tong Jiang; Lingfeng Dai; Hanlin Zhang; Chun Zou (Fuel, 2025)

Ultra-stable and pH-universal photoelectrochemical photodetector achieved by CdSeTe/ZnS core-shell quantum dots - Jian Zhang; Yule Zhang; Songrui We; Han Zhang; Lingfeng Gao; Hao Wang; Chunxian Guo (Chemical Engineering Journal, 2025)

Sulfur vacancy-rich ZnIn2S4 via solvent engineering: Unveiling structure-defect-activity relationships for photocatalytic ranitidine degradation - Yilan Wang; Lingfeng Ouyang; Shuai Zhang; Zhanghong Zhou; Carolina Belver; Season Si Chen; Hao Wu (Chemical Engineering Journal, 2025)

A data-driven multi-objective optimisation framework for energy efficiency and thermal comfort in flexible building spaces - Huanbo Lyu; Daniel Herring; Hongkuan Chen; Shiqiao Zhou; Jianyu Zhang; Lingfeng Wang; Zheming Zuo; James Andrews; Michal kočvara; Fabian Spill; Jelena Ninic; Shuo Wang (Energy and Buildings, 2025)

Devonian–Triassic tectonic evolution of the Western Qinling Orogenic Belt of central China: Insights from detrital zircon U Pb chronology and rock geochemistry - Yan Zhang; Shuang Dai; Futian Liu; Dongbao Guo; Lingfeng Qin; Zhongzhao Ding; Yongfa Chen; Xinnan Fang; Xiaojun Ma; Yu Wang; Hua Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Critical hydro-geomorphological characteristics related to lateral erosion–deposition difference within the multilevel bifurcation system of the Yangtze Estuary, China - Boyuan Zhu; Shiyu Zhang; Lingling Zhu; Lingfeng Liu; Wenjun Yu; Jinwu Tang; Yongzhou Cheng; Yitian Li; Alistair G.L. Borthwick (Journal of Hydrology, 2025)

Comparative analysis of machine learning based dissolved oxygen predictions in the Yellow River Basin: The role of diverse environmental predictors - Lingling Liu; Xiaoli Zhao; Lingfeng Zhou; Jiangtao Liu; Wenjing Li; Bolun Zhang; Junhong Ling; Fengchang Wu (Journal of Environmental Management, 2025)

The Ran GTPase inhibits SGIV and RGNNV infection by upregulating host immune response in grouper - Xiaozhi Wen; Lingfeng Guan; Liqun Wang; Zihan Zhang; Xinyan Wei; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2025)

Nano-magnetoelectric biomimetic system promotes neural differentiation and reverses dopaminergic neuron damage for Parkinson's disease therapy - Jie Zhang; Jiahui Shi; Qiubo Yang; Haogang Guo; Lingfeng Guo; Guoliang Zhou; Yinyi Liu; Xiaolei Wang; Xian Hao; Yifei Yang (Chemical Engineering Journal, 2025)

Ultrasensitive SERS detection of cytokines through specific binding and multiple reporter molecules - Hairong Chen; Hengchang Zhang; Lingfeng Duan; Kaidi Sun; Rui Li; Yunxia Wang; Jiacheng Yao; Changchun Yan; Ying Liu; Ying Wu; Guohai Yang; Caiqin Han (Analytica Chimica Acta, 2025)

Positive contributions of China's protected areas in biodiversity conservation and carbon storage under future climate change - Xuede Dong; Jirui Gong; Frank Yonghong Li; Lingfeng Mao; Weiyuan Zhang; Siqi Zhang; Guisen Yang; Chenyi Yan; Ruijing Wang; Shangpeng Zhang; Tong Wang (Science of The Total Environment, 2025)

Alleviating the work function of MoNi4/NiO heterostructures by stacking faults for enhanced hydrogen evolution reaction - Deli Tian; Junlin Yan; Lingfeng Yang; Min Xi; Youyu Long; Hua Zhang; Anran Chen (Chemical Engineering Journal, 2025)

Propagation characteristics of meteorological drought to hydrological drought in China - Ding Luo; Xiaoli Yang; Lingfeng Xie; Zhoubing Ye; Liliang Ren; Linyan Zhang; Fan Wu; Donglai Jiao (Journal of Hydrology, 2025)

Antarctic circumpolar current evolution and its relation to southern hemisphere westerly winds during the holocene - Lingfeng Wan; Dapeng Li; Chenyu Zhu; Zhengyu Liu; Shaoqing Zhang; Xiaopei Lin; Jiuyou Lu (Climate Dynamics, 2025)

In-situ atmospheric thermoelectric conversion on Mars - Yuzhuo Yang; Yonghao Zhang; Yu Yao; Gang Pei; Hua Tian; Lingfeng Shi; Gequn Shu (Science Bulletin, 2025)

Late Oligocene paleosols in the Haltang Basin of northeastern Tibetan Plateau and their implications for the early extent of the Asian monsoon - Zhaobin Zhang; Shuang Dai; Xinnan Fang; Xiaojun Ma; Yufan Zhang; Zhongzhao Ding; Lingfeng Qin; Chunyan Li; Meng Zhou; Tianqi Ji; Jie Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Sliding-window enhanced olfactory visual images combined with deep learning to predict TVB-N content in chilled mutton - Shichang Wang; Yixin Zhang; Rongguang Zhu; Fukang Xing; Jiufu Yan; Lingfeng Meng; Xuedong Yao (Meat Science, 2025)

Improving the efficiency of a CO2 heat pump for simultaneous heating and cooling coupled with an ambient source - Zhaoyang Yuan; Jintao He; Yonghao Zhang; Yu Yao; Hua Tian; Lingfeng Shi; Gequn Shu (International Journal of Refrigeration, 2025)

A hybrid cooling and power cogeneration scheme for broadening adaptability to distributed buildings: conceptual design, modeling, and operational assessment - Yonghao Zhang; Lingfeng Shi; Hua Tian; Jintao He; Yu Yao; Gequn Shu (Energy and Buildings, 2025)

Pressure-driven high-capacity lithium-carbon dioxide batteries - Tenghui Qiu; Xu Xiao; Zhuojun Zhang; Zehui Zhao; Aijing Yan; Yasen Hao; Lingfeng Shi; Peng Tan; Gequn Shu (Chemical Engineering Journal, 2025)

Temporal and spatial differentiation in the landslide sediment transfer potential in Wenchuan earthquake-impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Jiangang Chen; Tao Yang; Lingfeng Gong; Qingyun Shi; Xianzheng Zhang; Ning Li; Mingwei Li (Landslides, 2025)

Adaptation of Marine Heterotrophic Protists to Long‐Term Warming Selection - Mengwen Pang; Zuyuan Gao; Lingfeng Huang; Chuk Man Chan; Xiaodong Zhang; Ruilin Su; Ke Pan; Hongbin Liu (Global Change Biology, 2025)
The rise in surface ocean temperature imposes strong effects on marine organisms. With large population sizes and fast generation times, microorganisms may rapidly adapt to ocean warming. However, long‐term experimental adaptation studies on heterotrophic protists are very limited, hindering our comprehensive understanding of their adaptation capability and the underlying mechanisms. In this study, we conducted long‐term thermal selection experiments on six representative marine protozoa. By assessing their phenotypes, metabolism, thermal performance curves, thermal traits, and carbon allocation status, we found that all investigated heterotrophic protists exhibited a fitness‐improved adaptation response to warming scenarios. After growing in warmer conditions for hundreds of generations (~850 for Cafeteria burkhardae and ~500 for other species), their optimal temperature and maximum rates of both growth and ingestion increased, whereas respiration rates significantly decreased. In addition, the cell size, cellular carbon, and nitrogen content at an elevated environmental temperature also increased after warming adaptation. Mechanisms underlying the increased competitive fitness at high temperatures after warming adaptation might be associated with the alleviated oxidative stress, shown by the remarkable reduction in cellular reactive oxygen species contents. Our study, for the first time, reveals the ability of marine heterotrophic protists to adapt to higher temperatures, providing experimental support for predictive modeling studies that integrate evolutionary potential with short‐term physiological responses, with important implications for marine ecosystem functioning and biogeochemical cycling under global warming.

Yolk@Shell nanoreactors with spatial confinement cobalt species activate peroxymonosulfate for efficient degradation of bisphenol S - Ya Zeng; Lingfeng Qin; Sijie Tian; Caicheng Long; Taiping Qing; Peng Zhang; Bo Feng (Journal of Water Process Engineering, 2025)

Risk prediction of catastrophic debris flows against the background of material changes and human engineering activity in the Wenchuan earthquake disturbance area - Jiang Xiong; Huayong Chen; Chuan Tang; Wanyu Zhao; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Jiangang Chen (Bulletin of Engineering Geology and the Environment, 2025)

Multi-scale analysis of six evapotranspiration products across China: Accuracy, uncertainty and spatiotemporal pattern - Lingfeng Zuo; Lei Zou; Jun Xia; Liping Zhang; Hui Cao; Dunxian She (Journal of Hydrology, 2025)

Unlocking the effects of acid/alkali-catalyzed glycerol organosolv pretreatment on lignocellulosic biorefinery: Substrate digestibility and high-quality lignin - Lingfeng Long; Dongqin He; Tao Zhang; Xiaoxiao Chen; Xianzhi Meng; Arthur J. Ragauskas; Chen Huang (Bioresource Technology, 2025)

Exploring the relationship between walls and urban biodiversity: a systematic review - Qinghua Xu; Ranxu Jia; Ranyang Zhang; Yuncai Wang; Lingfeng Mao; Hui Wang (Urban Ecosystems, 2025)

Geomorphometric assessment of spatial transfer potential of landslides sediment in seismically impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Chenxiao Tang; Lingfeng Gong; Ming Chen; Xianzheng Zhang; Tao Yang; Ning Li; Qingyun Shi; Mingwei Li (Natural Hazards, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Co-infection of nervous necrosis virus and Vibrio harveyi increased mortality and worsened the disease severity in the orange-spotted grouper (Epinephelus coioides) - Lingfeng Guan; Xinshuai Li; Jinpeng Chen; Liqun Wang; Xinyue Zhang; Hongyan Sun; Yanwei Li; Min Yang; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2025)

ABTrans: A Transformer-based Model for Predicting Interaction between Anti-Aβ Antibodies and Peptides - Yuhong Su; Xincheng Zeng; Lingfeng Zhang; Yanlin Bian; Yangjing Wang; Buyong Ma (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Oral pH-Sensitive Solid Self-Microemulsion of Norcantharidin Wrapped in Colon-Coated Capsule for Selective Therapy of Colorectal Carcinoma - Xia Liu; Wenyou Fang; Wenjie Lu; Mingchao Xu; Zijun Wu; Dan Su; Lingzhen Ding; Qing Zhang; Jinguang Ouyang; Tianming Wang; Lingfeng Sun; Song Gao; et al. (AAPS PharmSciTech, 2025)

Dynamic impact of hillslope landslide sediment transfer to ecological environment recovery in earthquake disturbed area - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Mingwei Li (Bulletin of Engineering Geology and the Environment, 2025)

Causes of Atypical Meiyu in the Lower Yangtze River Basin in 2022: Subseasonal Perspective and Predictions - Zhiqi Zhang; Ping Liang; Yajing Liu; Yang Wu; Lingfeng Tao; Qi Chen; Yihui Ding (Journal of Meteorological Research, 2025)

Survival and physiological responses of pearl oyster Pinctada maxima seedlings: Comparative analysis of wet (submerged) and dry (waterless) transportation methods - Xing Zheng; Ze Yin; Lingfeng Wang; Shangkun Wei; Meng Zhang; Xinfei Shao; Hebert Ely Vasquez; Zhifeng Gu (Aquaculture, 2025)

Ion separation with graphene oxide nanofluidic membranes: A review - Dekang Pang; Lingfeng Liu; Xiaojing Zhang; Changsheng Guo; Jianbo Jia; Changyu Liu; Mengchen Zhang (Desalination, 2025)

Co-grown novel S-scheme tubular P–UCN/S-TCN homojunction mediates photocatalysis-PMS activation synergistic system for efficient degradation of antibiotic - Ting Wu; Zhifeng Liu; Binbin Shao; Yuan Pan; Qingyun He; Xiansheng Zhang; Lingfeng Zhou; Yunze Wang; Teng Li; Sheng Liu (Chemosphere, 2024)

Paleoclimate evolution of the Middle Triassic Guanling Formation from South China and its significance for the preservation of the Luoping biota - Zhongzhao Ding; Zhixin Ma; Shixue Hu; Shuang Dai; Qiyue Zhang; Xiao Min; Jinyuan Huang; Wen Wen; Changyong Zhou; Xinnan Fang; Tianqi Ji; Lingfeng Qin (Global and Planetary Change, 2024)

Double network hydrogel confined MXene/Liquid metal by dynamic hydrogen bond for high-performance wearable sensors - Yuanwan Lou; Jingkun Wang; Yubo Peng; Xiaona Wang; Jianan Zhang; Lingfeng Chen; Wenchao Gao; Zhipeng Gao; Xiaona Li; Weiyi Chen; Min Zhao (Chemical Engineering Journal, 2024)

The influence of digestive tract protein on cytotoxicity of polyvinyl chloride microplastics - Gonghao Liu; Qianwen Jiang; Lingfeng Qin; Zihang Zeng; Peng Zhang; Bo Feng; Xiaofeng Liu; Zhihe Qing; Taiping Qing (Science of The Total Environment, 2024)

Increased microgastropoda sampling give new insights into the phylogenetic relationships of Littorinoidea (Littorinimorpha) - Lu Qi; Ning Zhang; Biyang Xu; Qinzeng Xu; Xiao Han; Lingfeng Kong; Qi Li (Molecular Phylogenetics and Evolution, 2024)

Janus graphene oxide membrane with rational allocation of functional regions as unidirectional ion valve system - Jundong Yan; Lingfeng Liu; Zhichen Liang; Chongfeng Huang; Wenbiao Zheng; Changsheng Guo; Minchao Liu; Chao Peng; Jianbo Jia; Mengchen Zhang (Desalination, 2024)

Bioorthogonal surface-edited exosomes for targeted multimodal imaging and synergic chemophototherapy of oral cancer - Yuxiao Wu; Xiaofeng Shan; Yuanjie Zhang; Wen Shi; Xingxing Zhu; Mengfan Yu; Shang Xie; Lingfeng Guo; Zhiqian Chen; Chuanling Zhang; Demin Zhou; Zhigang Cai (Chemical Engineering Journal, 2024)

Comparison of the toxic effects of polystyrene and sulfonated polystyrene on wheat under cadmium stress - Lingfeng Qin; Gonghao Liu; Jiaoyan Huang; Zihang Zeng; Ya Zeng; Taiping Qing; Peng Zhang; Bo Feng (Journal of Hazardous Materials, 2024)

A multiplex method for the detection of food microorganisms based on suspension microarrays combined with recombinase-aided amplification - Wentao Zeng; Xihao Fan; Azadeh Nilghaz; Gengfen Zhao; Lingfeng Yan; Zhuoxuan Lu; Liming Zhang (Food Bioscience, 2024)

Influence of corrosion on seismic performance of steel beam-to-column connections - Yuelin Zhang; Cheng Fang; Wei Wang; Lingfeng Wu; Peng Cao (Engineering Structures, 2024)

Catastrophic debris flow triggered by a June 26, 2023 rainstorm suggests the debris flow is still active 15 years after the Wenchuan seismic - Huayong Chen; Jiang Xiong; Wanyu Zhao; Jiangang Chen; Xianzheng Zhang; Hechun Ruan; Congxi Fang; Lingfeng Gong (Landslides, 2024)

Dynamic susceptibility assessment of debris flow hazard after a strong earthquake, Wenchuan County, Sichuan, China - Xianzheng Zhang; Chenxiao Tang; Yongbo Tie; Xiaojuan Li; Chuan Tang; Jiang Xiong; Ming Chen; Lingfeng Gong (Landslides, 2024)

Cation-driven self-assembly of core–shell covalent organic frameworks@Ti3CN MXene nanospheres for high-performance aqueous zinc-ion hybrid supercapacitors - Kaige Zhang; Quan Zong; Kuixing Ding; Ying Wang; Lingfeng Gao; Dongdong Xu; Zhonghui Chen; Huanan Yu (Chemical Engineering Journal, 2024)

Wide-bandgap donor polymers from organic photovoltaics as dopant-free hole transport layers for perovskite solar cells - Hongtao Lai; Xin Yang; Liujiang Zhang; Leyu Bi; Binqiang Tian; Huanhuan Wang; Xingyu Gao; Lingfeng Lu; Bin Kan; Xiaofei Ji; Qiang Fu (Chemical Engineering Journal, 2024)

Relationship between eutrophication and greenhouse gases emission in shallow freshwater lakes - Jingjie Zhang; Lingfeng Cao; Zhenghan Liu; Lingling Wan; Xiuyun Cao; Yiyong Zhou; Chunlei Song (Science of The Total Environment, 2024)

Nanofiltration membrane with modified nano-gradient structure and positive charge for Li separation from high Mg/Li ratio brine - Peng Zhao; Fei Guo; Lingfeng Wang; Huange Zhen; Ning Zhang; Shaohua Yin; Guoli Zhou; Xuehua Ruan; Gaohong He; Xiaobin Jiang (Desalination, 2024)

Seipin Deficiency Leads to Energy Dyshomeostasis via Inducing Hypothalamic Neuroinflammation and Aberrant Expression of Neuropeptides - Wenli Cui; Hong Chen; Lingfeng Lei; Wenru Wang; Kah-Leong Lim; Chengwu Zhang; Li Lu (NeuroMolecular Medicine, 2024)

Advancing C5+ hydrocarbons fuels production: An interpretable machine learning framework for Co-catalyzed syngas conversion - Zhilong Yuan; Ye Wang; Lingfeng Zhu; Congcong Zhang; Yifei Sun (Fuel, 2024)

Differences in the activities of six soil enzymes in response to cadmium contamination of paddy soils in high geological background areas - Juan Liu; Xinyang Li; Qilin Zhu; Jiawen Zhou; Lingfeng Shi; Weihong Lu; Li Bao; Lei Meng; Longhua Wu; Naiming Zhang; Peter Christie (Environmental Pollution, 2024)

Impact of Cross-Limb Stent-Graft Configuration on Hemodynamics in Abdominal Aortic Aneurysm Interventional Therapy - Yanqing Xie; Yating Zhu; Yike Shi; Yawei Zhao; Hongpeng Zhang; Fen Li; Hui Song; Lingfeng Chen; Wei Guo (Cardiovascular Engineering and Technology, 2024)

Prediction of debris flow blocking river hazard chain by the numerical simulation: the Cutou catchment, Wenchuan County, China - Xianzheng Zhang; Yongbo Tie; Chenxiao Tang; Yajie Yu; Lingfeng Gong; Jiang Xiong (Bulletin of Engineering Geology and the Environment, 2024)

Responses of microeukaryotic community structure to a Phaeocystis globosa bloom in a semi-enclosed subtropical bay - Beibei Han; Rongjun Shi; Shufei Zhang; Anji Lian; Zexing Kuang; Fengxia Wu; Lingfeng Huang; Honghui Huang (Marine Environmental Research, 2024)

Differentiation of fungal trophic guilds to long-term nitrogen addition in a poplar plantation - Nan Yang; Jiangbao Zhang; Jiani Hua; Baohan Song; Tianyi Wang; Wei Xing; Guobing Wang; Lingfeng Mao; Honghua Ruan (Forest Ecology and Management, 2024)

Effects of cadmium exposure during pregnancy on genome-wide DNA methylation and the CREB/CREM pathway in the testes of male offspring rats - Xiushuai Du; Jianlin Zhu; Xueming Xu; Zhilan Lu; Xiaoqin Li; Yuchen Li; Lingfeng Luo; Wenchang Zhang; Jin Liu (Chemosphere, 2024)

MOF derived MnFeOX supported on carbon cloth as electrochemical anode for peroxymonosulfate electro-activation and persistent organic pollutants degradation - Xiansheng Zhang; Yuan Pan; Yunze Wang; Ting Wu; Binbin Shao; Qingyun He; Lingfeng Zhou; Teng Li; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Application of 3D hierarchical porous NiCo-spinel nanosheet array for enhancement of synergistic activation of peroxymonosulfate: Degradation, Intermediates, mechanism and degradation pathway of tetracycline - Yuan Pan; Xiansheng Zhang; Ting Wu; Binbin Shao; Teng Li; Qingyun He; Zehua Chen; Lingfeng Zhou; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

More than just pandas: Urgent research needed on China's native plant biodiversity - Yu-heng Chen; Yao Li; Yu-ran Dong; Min Zhang; Yong Yang; Richard B. Primack; Kathryn E. Barry; Lingfeng Mao (Biological Conservation, 2024)

Revealing the specificity of map method to predict the performance of a combined cooling and power cycle under operating conditions - Yu Yao; Lingfeng Shi; Jintao He; Xiaocun Sun; Bowen Lu; Yonghao Zhang; Hua Tian; Xuan Wang; Gequn Shu (Journal of Cleaner Production, 2023)

Grouper Rab1 inhibits nodovirus infection by affecting virus entry and host immune response - Lingfeng Guan; Xiaozhi Wen; Zihan Zhang; Liqun Wang; Xinyue Zhang; Min Yang; Shaowen Wang; Qiwei Qin (Fish & Shellfish Immunology, 2023)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

Interfacial electronic engineering of heterostructured Co2P-MoNiP/NF nano-sea-urchin catalysts for efficient and stable hydrogen evolution via water/seawater splitting - Yifan Zhao; Hua Zhang; Ji Chen; Shuwen Zhao; Min Xi; Lingfeng Yang; Youyu Long; Zitao Ni; Yao Zhou; Anran Chen (Chemical Engineering Journal, 2023)

An improved frequency-domain model for the supercritical flow instability analysis in vertical tubes - Lingfeng Bi; Xirong Zhang; Weiteng Li; Tingyu Chen; Xiaocheng Du; Dong Yang (Annals of Nuclear Energy, 2023)

Application of remote sensing monitoring to the spatiotemporal variation in debris flow activity in the catastrophic Wenchuan seismic area - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Ming Chang; Xianzheng Zhang; Lingfeng Gong; Ning Li; Qingyun Shi; Mingwei Li (CATENA, 2023)

Environment drives the co-occurrence of bacteria and microeukaryotes in a typical subtropical bay - Yifan Ma; Lingfeng Huang; Wenjing Zhang (Journal of Oceanology and Limnology, 2023)

Parallel evolution in Crassostrea oysters along the latitudinal gradient is associated with variation in multiple genes involved in adipogenesis - Wen Teng; Huiru Fu; Zhuanzhuan Li; Qian Zhang; Chengxun Xu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Molecular Ecology, 2023)
Parallel diversification provides a proper framework for studying the role of natural selection in evolution. Yet, empirical studies from ecological ‘non‐model’ species of invertebrates are limited at the whole genome level. Here, we presented a chromosome‐scale genome assembly for Crassostrea angulata and investigated the parallel genomic evolution in oysters. Specifically, we used population genomics approaches to compare two southern–northern oyster species pairs ( C . angulata – C . gigas and southern–northern C . ariakensis ) along the coast of China. The estimated divergence time of C . angulata and C . gigas is earlier than that of southern and northern C . ariakensis , which aligns with the overall elevated genome‐wide divergence. However, the southern–northern C . ariakensis F ST profile represented more extremely divergent “islands”. Combined with recent reciprocal hybridization studies, we proposed that they are currently at an early stage of speciation. These two southern–northern oyster species pairs exhibited significant repeatability in patterns of genome‐wide differentiation, especially in genomic regions with extremely high and low divergence. This suggested that divergent and purifying selection has contributed to the genomic parallelism between southern and northern latitudes. Top differentiated genomic regions shared in these two oyster species pairs contained candidate genes enriched for functions in energy metabolism, especially adipogenesis, which are closely related to reproductive behaviours. These genes might be good candidates for further investigation in vivo. In conclusion, our results suggest that similar divergent selection and shared genomic features could predictably transform standing genetic variation within one species pair into differences in another.

Solvent effect to modulate nitrogen dopant in Co-N-C catalysts for oxygen reduction reaction acceleration - Lingfeng Li; Guokang Han; Yandi Wen; Yuxin Liu; Rang Xiao; Wei Zhang; Fanpeng Kong; Lei Du; Yulin Ma; Pengjian Zuo; Chunyu Du; Geping Yin (Fuel, 2023)

Low-photovoltage-loss pringting perovskite solar cells in ambient air through ink synergistic engineering - Yifan Lv; Kaiyu Wang; Ai Lan; Lingfeng Chao; Changshun Chen; Jinpei Wang; Qing Yao; Jianxin Chen; Tengfei Pan; Yajing Li; Hui Zhang; Yingdong Xia; et al. (Chemical Engineering Journal, 2023)

Effect of extreme pH conditions on methanogenesis: Methanogen metabolism and community structure - Shuang Qiu; Xingchen Zhang; Wenhao Xia; Zimu Li; Lingfeng Wang; Zhipeng Chen; Shijian Ge (Science of The Total Environment, 2023)

Investigating the spatial–temporal changes of flood events across the Yangtze River Basin, China: Identification, spatial heterogeneity, and dominant impact factors - Jiarui Yu; Lei Zou; Jun Xia; Yongyong Zhang; Lingfeng Zuo; Xiaoyang Li (Journal of Hydrology, 2023)

Synergistic structure of LiFeO2 and Fe2O3 layers with electrostatic shielding effect to suppress surface lattice oxygen release of Ni-rich cathode - Youqi Chu; Yongbiao Mu; Lingfeng Zou; Jie Cheng; Shibo Xi; Qichang Pan; Meisheng Han; Hongqiang Wang; Qingyu Li; Fenghua Zheng; Qing Zhang; Lin Zeng (Chemical Engineering Journal, 2023)

Spatio-temporal heterogeneity in the international trade resilience during COVID-19 - Wei Luo; Lingfeng He; Zihui Yang; Shirui Zhang; Yong Wang; Dianbo Liu; Sheng Hu; Li He; Jizhe Xia; Min Chen (Applied Geography, 2023)

Surface display of major capsid protein on Bacillus subtilis spores against largemouth bass virus (LMBV) for oral administration - Quan Wang; Xia Liang; Yunshang Ning; Shijia Liu; Zengjian Liang; Zemiao Zhang; Yingjing Chen; Jinqiao Cao; Fubao Wang; Lingfeng Lan; Guangzhao Cheng; Youhua Huang; et al. (Fish & Shellfish Immunology, 2023)

Paternal genetic intergenerational and transgenerational effects of cadmium exposure on hormone synthesis disorders in progeny ovarian granulosa cells - Yi Sun; Chenyun Zhang; Lingfeng Luo; Hao Lin; Chenchen Liu; Wenchang Zhang (Environmental Pollution, 2023)

Ultrasonic Sensor-Based Basecutter Height Control System of Sugarcane Harvester - Zhengliang Ding; Shaochun Ma; Xiadong Zhang; Wenpeng Liang; Lingfeng Li; Chenyang Su (Sugar Tech, 2023)

The function of γδ T cells in humoral immune responses - Lingfeng Qiu; Yixi Zhang; Xun Zeng (Inflammation Research, 2023)

Degradation of PAHs in soil by activated persulfate system with activated carbon supported iron-based bimetal - Congcong Zhang; Huifang Tian; Zhaoxu Wang; Lingfeng Zhu; Xingshuang Liu; Ye Wang; Yifei Sun (Science of The Total Environment, 2023)

Remediation of uranium-contaminated alkaline soil by rational application of phosphorus fertilizers: Effect and mechanism - Lingfeng Dong; Zhanfei He; Jingyi Wu; Keqing Zhang; Daoyong Zhang; Xiangliang Pan (Environmental Research, 2023)

A self-powered wearable piezoelectric nanogenerator for physiological monitoring based on lead zirconate titanate/microfibrillated cellulose@polyvinyl alcohol (PZT/MFC@PVA) composition - Yanfang Guan; Mingyang Bai; Qilong Wang; Lei Liu; Shaobo Yu; Bingru Kong; Feng Lv; Mingshuo Guo; Guangyu Liu; Lingfeng Li; Lin Zhang; Yang Lin; et al. (Chemical Engineering Journal, 2023)

Chronic exposure to IQOS results in impaired pulmonary function and lung tissue damage in mice - Jianjun Gu; Daohui Gong; Yuxiu Wang; Tingting Feng; Jun Zhang; Suwei Hu; Lingfeng Min (Toxicology Letters, 2023)

Interaction among soil nutrients, plant diversity and hypogeal fungal trophic guild modifies root-associated fungal diversity in coniferous forests of Chinese Southern Himalayas - Nan Yang; Yan Zhang; Jingji Li; Xiuxiu Li; Honghua Ruan; Parag Bhople; Katharina Keiblinger; Lingfeng Mao; Dong Liu (Plant and Soil, 2022)

Correction: Mucus-Penetrating Alginate-Chitosan Nanoparticles Loaded with Berberine Hydrochloride for Oral Delivery to the Inflammation Site of Ulcerative Colitis - Lingfeng Sun; Xiangjiang Nie; Wenjie Lu; Qing Zhang; Wenyou Fang; Song Gao; Shengqi Chen; Rongfeng Hu (AAPS PharmSciTech, 2022)

Mucus-Penetrating Alginate-Chitosan Nanoparticles Loaded with Berberine Hydrochloride for Oral Delivery to the Inflammation Site of Ulcerative Colitis - Lingfeng Sun; Xiangjiang Nie; Wenjie Lu; Qing Zhang; Wenyou Fang; Song Gao; Shengqi Chen; Rongfeng Hu (AAPS PharmSciTech, 2022)

Determination of trophic levels of marine fish in the Yellow Sea and northern East China Sea using nitrogen stable isotope (δ15N) analysis of otoliths - Huaiyu Bai; Yukun Wang; Tingting Zhang; Fangqun Dai; Lingfeng Huang; Yao Sun (Journal of Oceanology and Limnology, 2022)

Erratum to: Contribution of Water Vapor to the Record-Breaking Extreme Meiyu Rainfall along the Yangtze River Valley in 2020 - Licheng Wang; Xuguang Sun; Xiu-Qun Yang; Lingfeng Tao; Zhiqi Zhang (Journal of Meteorological Research, 2021)

Niche overlap and divergence times support niche conservatism in eastern Asia–eastern North America disjunct plants - Xue Yin; Scott Jarvie; Wen‐Yong Guo; Tao Deng; Lingfeng Mao; Minhua Zhang; Chengjin Chu; Hong Qian; Jens‐Christian Svenning; Fangliang He (Global Ecology and Biogeography, 2021)
Aim The plant species sharing ancestors now disjunctly distributed in eastern Asia (EAS) and eastern North America (ENA) have long been a biogeographic puzzle. Species within the EAS–ENA disjunct genera are presumed to exhibit niche conservatism, the tendency of closely related species to be more ecologically similar, reflecting lineages’ common evolutionary history. However, the hypothesis has not been well examined at the species level. Location EAS and ENA. Time period Current. Major taxa studied Species within the EAS–ENA disjunct genera. Methods We compiled data on climate, species occurrence, growth form, and phylogeny to examine niche conservatism. We first built a phylogenetic tree to select intercontinental congeneric pairwise species and obtained their divergence times. We then quantified the observed niche overlaps with Schoener’s D , which has a 0–1 range, based on species occurrence and climate of species’ native ranges. To obtain projected distributions, each species’ niche was projected to the non‐native region using ensemble ecological niche models. Projected‐related niche overlaps were then calculated using projected distributions and the corresponding climatic conditions. Results Average observed niche overlaps of congeneric pairwise species were relatively small: .124, .211 and .109 for all, herbaceous and woody species, respectively. Both observed and projected‐related niche overlaps had significant negative relationships with divergence times of intercontinental congeneric pairwise species, with niche overlap for herbaceous species being higher than that for woody plants when controlling for divergence times. Main conclusions We conclude that the significant negative relationships between niche overlap and divergence times of congeneric pairwise species confirm niche conservatism among species of EAS–ENA disjunct plants and that the extent of niche conservatism is slightly different for herbaceous and woody plants. These findings suggest the potential role of allopatric speciation in EAS, and could help to understand the evolutionary history and the Asian‐bias diversity pattern of the EAS–ENA disjunct plants.

Effects of climate and topography on the diversity anomaly of plants disjunctly distributed in eastern Asia and eastern North America - Xue Yin; Hong Qian; Xinghua Sui; Minhua Zhang; Lingfeng Mao; Jens‐Christian Svenning; Robert E. Ricklefs; Fangliang He (Global Ecology and Biogeography, 2021)
Aim Differences in physiography have been proposed to explain the diversity anomaly for vascular plants between environmentally similar regions of eastern Asia (EAS) and eastern North America (ENA). Here, we use plant species within disjunct genera to examine whether differences in topography contribute to the diversity anomaly and whether the richness–environment relationships differ between regions. Disjunct plants are used to ensure that the diversity anomaly relates to post‐disjunction evolution and diversification rather than regional differences in clade ages or immigration. Location EAS and ENA. Time period Current. Major taxa studied Plant taxa disjunctly distributed in EAS and ENA. Methods We compiled county‐level plant distribution data, and calculated species richness and variables of topography and climate within unit grid cells. We compared estimated coefficients of region effects among models, where richness was fitted with or without topography and climate. Topography and climate were also used to separately model within‐region spatial diversity patterns using spatial simultaneous autoregressive error models. Results The coefficients of region effects varied from −.776 for the model only including region to −.309 when topography was controlled for, but remained significant. Climate dominated the spatial diversity patterns in ENA. In contrast, the influence of climate (14.2%) on species richness was weaker than that of topography (18.3%) in the warm area of EAS. Relations to elevation and temperature varied between regions, shifting between positive and negative relationships in several cases. Main conclusions Our results demonstrate that variability in local topography contributes to the strong regional anomaly in plant species richness between EAS and ENA. Nevertheless, the diversity anomaly persists after controlling for local topography and climate. EAS and ENA also exhibit contrasting richness–environment relationships, providing another divergent aspect between the EAS–ENA disjunct floras. Our findings highlight that regional differences in topography or other environmental factors may underlie the diversity anomaly.

Faster recovery of soil biodiversity in native species mixture than in Eucalyptus monoculture after 60 years afforestation in tropical degraded coastal terraces - Wenjia Wu; Luhui Kuang; Yue Li; Lingfeng He; Zhijian Mou; Faming Wang; Jing Zhang; Jun Wang; Zhi’an Li; Hans Lambers; Jordi Sardans; Josep Peñuelas; et al. (Global Change Biology, 2021)
Afforestation is an effective method to restore degraded land. Afforestation methods vary in their effects on ecosystem multifunctionality, but their effects on soil biodiversity have been largely overlooked. Here, we mapped the biodiversity and functioning of multiple soil organism groups resulting from diverse afforestation methods in tropical coastal terraces. Sixty years after afforestation from bare land (BL), plant species richness and the abundance of plant litter (398 ± 85 g m −2 ) and plant biomass (179 ± 3.7 t ha −1 ) in native tree species mixtures (MF) were restored to the level of native forests (NF; 287 ± 21 g m −2 and 243.0 ± 33 t ha −1 , respectively), while Eucalyptus monoculture (EP) only successfully restored the litter mass (388 ± 43 g m −2 ) to the level of NF. Soil fertility in EP and MF was increased but remained lower than in NF. For example, soil nitrogen and phosphorus concentrations in MF (1.2 ± 0.2 g kg −1 and 408 ± 49 mg kg −1 , respectively; p −1 and 523 ± 24 mg kg −1 , respectively; p

Molecular Identification of Dried Shellfish Products Sold on the Market Using DNA Barcoding - Shao’e Sun; Xiaojie Zhang; Lingfeng Kong; Qi Li (Journal of Ocean University of China, 2021)

Contribution of Water Vapor to the Record-Breaking Extreme Meiyu Rainfall along the Yangtze River Valley in 2020 - Licheng Wang; Xuguang Sun; Xiuqun Yang; Lingfeng Tao; Zhiqi Zhang (Journal of Meteorological Research, 2021)

Regional disparity in extinction risk: Comparison of disjunct plant genera between eastern Asia and eastern North America - Houjuan Song; Alejandro Ordonez; Jens‐Christian Svenning; Hong Qian; Xue Yin; Lingfeng Mao; Tao Deng; Jian Zhang (Global Change Biology, 2021)
Climate and land cover changes are increasing threats to biodiversity globally. However, potentially varying biotic sensitivity is a major source of uncertainty for translating environmental changes to extinction risks. To reduce this uncertainty, we assessed how extinction risks will be affected by future human‐driven environmental changes, focusing on 554 species from 52 disjunct plant genera between eastern Asia (EAS) and eastern North America (ENA) to control for differences in environmental sensitivity at the genus level. Species distribution models were used to estimate and compare the vulnerability of species in disjunct genera between the two regions under two climate and land cover change scenarios (RCP2.6 and RCP8.5) in the 2070s, allowing to assess the effects of differences in climate and land cover pressures. Compared with ENA, stronger pressures from climate and land cover changes along with smaller range sizes in EAS translate into a larger number and proportion of species in disjunct genera becoming threatened by the 2070s. These regional differences are more pronounced under a best‐case climate scenario (RCP2.6), illustrating that strong climate change (RCP8.5) may override any regional buffer capacities. The main variables determining extinction risks differed between the two continental regions, with annual temperature range and cropland expansion being important in EAS, and annual precipitation being important in ENA. These results suggest that disparities in regional exposure to anthropogenic environmental changes may cause congeneric species with relatively similar sensitivity to have different future risks of extinction. Moreover, the findings highlight the context‐specific nature of anthropogenic effects on biodiversity and the importance of making region‐specific policies for conservation and restoration in response to the intensifying global changes.

Assessment of uranium migration and pollution sources in river sediments of the Ili River Basin using multiply statistical techniques - Lingfeng Dong; Zhanfei He; Fan Zhang; Tao Xu; Jingyi Wu; Kaifang Yan; Xiangliang Pan; Daoyong Zhang (Environmental Science and Pollution Research, 2021)

Activity characteristics and enlightenment of the debris flow triggered by the rainstorm on 20 August 2019 in Wenchuan County, China - Jiang Xiong; Chuan Tang; Ming Chen; Xianzheng Zhang; Qingyun Shi; Lingfeng Gong (Bulletin of Engineering Geology and the Environment, 2021)

Seasonal and Spatial Variation of Pelagic Microbial Food Web Structure in a Semi-Enclosed Temperate Bay - Haibo Li; Xue Chen; Michel Denis; Yuan Zhao; Lingfeng Huang; Zengjie Jiang; Wuchang Zhang; Tian Xiao (Frontiers in Marine Science, 2020)

Grazing by microzooplankton and copepods on the microbial food web in spring in the southern Yellow Sea, China - Yuan Zhao; Yi Dong; Haibo Li; Shiquan Lin; Lingfeng Huang; Tian Xiao; Gerald Gregori; Li Zhao; Wuchang Zhang (Marine Life Science & Technology, 2020)
Assessment of microzooplankton and copepods grazing pressure on picoplankton is a key requirement for resolving the microbial food web efficiency. Although microzooplankton grazing on picoplankton has been extensively studied, the impact of microzooplankton on different groups of picoplankton, i.e., heterotrophic bacteria, Synechococcus and picoeukaryotes have rarely been compared. Furthermore, in the very few existing studies there is no consistent evidence of an enhancing or restraining effect of copepods on picoplankton. More studies are needed to improve our understanding of the influence of microzooplankton and copepod on picoplankton. Dilution incubations and copepod addition incubations were performed during a cruise to the southern Yellow Sea on May 16–29, 2007. The bulk grazing of microzooplankton and the calanoid copepod Calanus sinicus on phytoplankton, flagellates and picoplankton was estimated. Stations were divided into either eutrophic or oligotrophic according to the nutrient and biological parameters. Picoplankton comprised a large part of the diet of microzooplankton in the central oligotrophic area, while phytoplankton was the main food of microzooplankton in the coastal eutrophic area. In the central oligotrophic area, microzooplankton preferred grazing on Synechococcus . After copepod addition, ciliate abundance decreased while Synechococcus abundance increased (382%, 64% and 64% at three experimental stations, respectively), indicating strong grazing pressure of microzooplankton on Synechococcus . Our results suggest that Synechococcus might be an essential carbon source the planktonic food web in the oligotrophic waters of southern Yellow Sea.

The geographic and climatic distribution of plant height diversity for 19,000 angiosperms in China - Lingfeng Mao; Nathan G. Swenson; Xinghua Sui; Jinlong Zhang; Shengbin Chen; Jingji Li; Peihao Peng; Guangsheng Zhou; Xinshi Zhang (Biodiversity and Conservation, 2020)

DNA methylation frequency and epigenetic variability of the Pacific oyster Crassostrea gigas in relation to the gametogenesis - Xin Zhang; Qi Li; Lingfeng Kong; Hong Yu (Fisheries Science, 2018)

The impact of successive mass selection on population genetic structure in the Pacific oyster (Crassostrea gigas) revealed by microsatellite markers - Jingxiao Zhang; Qi Li; Qingzhi Wang; Rihao Cong; Jianlong Ge; Lingfeng Kong (Aquaculture International, 2018)

Epigenetic variation of wild populations of the Pacific oyster Crassostrea gigas determined by methylation-sensitive amplified polymorphism analysis - Xin Zhang; Qi Li; Lingfeng Kong; Hong Yu (Fisheries Science, 2018)

DNA methylation changes detected by methylation-sensitive amplified polymorphism in the Pacific oyster (Crassostrea gigas) in response to salinity stress - Xin Zhang; Qi Li; Lingfeng Kong; Hong Yu (Genes & Genomics, 2017)

QSAR modeling and in silico design of small-molecule inhibitors targeting the interaction between E3 ligase VHL and HIF-1 $$α $$ α - Jing Pan; Yanmin Zhang; Ting Ran; Anyang Xu; Xin Qiao; Lingfeng Yin; Weineng Zhou; Lu Zhu; Junnan Zhao; Tao Lu; Yadong Chen; Yulei Jiang (Molecular Diversity, 2017)

Chitosan scaffolds induce human dental pulp stem cells to neural differentiation: potential roles for spinal cord injury therapy - Jinlong Zhang; Xiaohui Lu; Guijuan Feng; Zhifeng Gu; Yuyu Sun; Guofeng Bao; Guanhua Xu; Yuanzhou Lu; Jiajia Chen; Lingfeng Xu; Xingmei Feng; Zhiming Cui (Cell and Tissue Research, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Spatial patterns and environmental correlates of bryophyte richness: sampling effort matters - Shengbin Chen; J. W. Ferry Slik; Lingfeng Mao; Jian Zhang; Rula Sa; Kexin Zhou; Jixi Gao (Biodiversity and Conservation, 2015)

Expanded Flap to Repair Facial Scar Left by Radiotherapy of Hemangioma - Donghong Zhao; Xinrong Ma; Jiang Li; Lingfeng Zhang; Baozhen Zhu (Cell Biochemistry and Biophysics, 2014)

Environmental determinants of geographic butterfly richness pattern in eastern China - Shengbin Chen; Lingfeng Mao; Jinlong Zhang; Kexin Zhou; Jixi Gao (Biodiversity and Conservation, 2014)

Microbial community of aerobic granules for ammonium and sulphide removal in a sequencing batch reactor - Caili Su; Lingfeng Zhu; Chuan Zhang; Xianghui Qi; Yiping Guo; Ruqin Gao (Biotechnology Letters, 2012)

Cloning and Characterization of a Novel Human Prefoldin and SPEC Domain Protein Gene (PFD6L) From the Fetal Brain - Jiayi Zhang; Lingfeng Liu; Xiaomeng Zhang; Feng Jin; Jinzhong Chen; Chaoneng Ji; Shaohua Gu; Yi Xie; Yumin Mao (Biochemical Genetics, 2006)